Cross-species physiological assessment of brain estrogen receptor expression using (18)F-FES and (18)F-4FMFES PET imaging - Paquette, Michel (Mol Imaging Biol, 2020)
PURPOSE: A retrospective analysis was performed of preclinical and clinical data acquired during the evaluation of the estrogen receptor (ER) PET tracer 4-fluoro-11β-methoxy-16α-[(18)F]-fluoroestradiol (4FMFES) and its comparison with 16α-[(18)F]-fluoroestradiol (FES) in mice, rats and humans with a focus on the brain uptake. PROCEDURES: Breast cancer tumor-bearing female BALB/c mice from a previous study and female Sprague-Dawley rats (control and ovariectomized) were imaged by 4FMFES or FES-PET imaging. Immediately after, low-dose CT was performed in the same bed position. Semi-quantitative analysis was conducted to extract %ID/g data. Small cohorts of mice and rats were imaged with 4FMFES in an ultra-high-resolution small animal PET scanner prototype (LabPET II). Rat brains were dissected and imaged separately with both PET and autoradiography. In parallel, 31 breast cancer patients were enrolled in a clinical phase II study to compare 4FMFES with FES for oncological assessment. Since the head was included in the field-of-view, brain uptake of discernable foci was measured and reported as SUV(Max). RESULTS: Regardless of the species studied, 4FMFES and FES uptake was relatively uniform in most regions of the brain, except for bilateral foci at the base of the skull, at the midsection of the brain. Anatomical localization of the PET signal using CT image fusion indicates that the signal origins from the pituitary in all studied species. 4FMFES yielded lower pituitary uptake than FES in patients, but an inverse trend was observed in rodents. 4FMFES pituitary contrast was higher than FES in all assessed groups. High-resolution small animal imaging of the brain of rats and mice revealed a supplemental signal anterior to the pituitary, which is likely to be the medial preoptic area. Dissection data further confirmed those findings and revealed additional signals corresponding to the arcuate and ventromedial nuclei, along with the medial and cortical amygdala. CONCLUSION: 4FMFES allowed visualization of ER expression in the pituitary in humans and two different rodent species with better contrast than FES. Improvement in clinical spatial resolution might allow visualization and analysis of other ER-rich brain areas in humans. Further work is now possible to link 4FMFES pituitary uptake to cognitive functions.